TEKNOLOGI PENGOLAHAN TEH HERBAL DARI TANAMAN GAHARU DI KELURAHAN LAMBUNG BUKIK KOTA PADANG - Benni Satria; Nilla Kristina; Afrima Sari; Indra Dwipa; Armansyah Armansyah; Syahyana Raesi; Ferry Lismanto Syaiful; Trizelia Trizelia (Jurnal Hilirisasi IPTEKS, 2020)
The majority of Lambung Bukik Village people, Pauh Subdistrict, Padang City, make a living from farming horticultural crops, secondary crops, forest plants (Sungkai and gaharu) and raising cattle and chickens. The Sungkai Permai Farmer Group has a 2-5-year-old gaharu tree, the seeds obtained through the Elok Nagari CSR activities of PT Semen Padang. Currently, the agarwood tree has good potential through the inoculation of fungal pathogens on the agarwood tree to form economically valuable sapwood and the use of its leaves as a health drink. This activity aims to: 1). the community knows how to cultivate agarwood plants, know its benefits, and know-how to process parts of the agarwood tree, such as sapwood and leaves, into raw materials for tea drinks, 2). provide special skills for farmer groups members so that they are expected to be used as independent businesses; 3). They empower the community in utilizing empty land through the cropping pattern of aloes agroforestry with plantation crops, 4). as a form of community activity from Andalas University, especially the Faculty of Agriculture. This activity was carried out in the Sungkai Permai Farmer Group, Lambung Bukik Village, Padang City. The Sungkai Permai farmer group has acquired knowledge about gaharu cultivation and tea use through participatory methods and training in the form of demonstrations and demonstration plots by planting approximately 150 gaharu seeds as raw material for tea through an agroforestry pattern. The Sungkai Permai farmer group has acquired knowledge of using the part of gaharu to become aloe tea as a drink and health medicine from the leaves and sap of aloes. The Sungkai Permai farmer group can manage raw materials for gaharu leaves and sap derived from gaharu trees around farmers' land in Limau Manis sub-district, or other areas. They can be a productive business opportunity as tea and medicine in health drinks to improve the community's economy.